Old Dog, New Trick: Efficacy of Self-Directed Procedural Training for Attending Critical Care Physicians. (April 2022) - Reaven, Matthew; Connor-Schuler, Randi; Bender, William; Daniels, Lisa
Background: In teaching hospitals, the majority of central venous lines (CVL) are placed by trainees, resulting in little opportunity for attending critical care physicians to maintain this procedural skill. Additionally, not all attending critical care physicians have been trained in the most up-to-date method of dynamic ultrasound (US) guided CVL placement. Furthermore, there is no standardized method to assess procedural competency of attending critical care physicians or to train them in the evolving practice of CVL placement. Despite these limitations, attending critical care physicians are ultimately responsible for supervision of CVL placement by trainees. Objective: To assess the utility of an instructional video to impact attending critical care physicians' competency and confidence in dynamic US guided CVL placement. Methods: A pre-post intervention study was conducted at an academic medical center. Attending critical care physicians were first asked to obtain CVL access on a gelatin model using US guidance. They then participated in the intervention, which consisted of watching a short instructional video demonstrating a method of dynamic US guided CVL placement. They were then asked to obtain access again, this time using the described method. All CVL placements were video recorded to assess competency in dynamic US guided CVL placement as well as the time required to obtain CVL access. Two blinded and independent reviewers evaluated each video with discrepancies resolved by a third reviewer. Participants were also surveyed pre and post intervention to assess their confidence in performing and supervising CVL placement. Results: A total of 21 attending critical care physicians were included. Pre-intervention, four used dynamic US guidance compared to 16 post-intervention ( P < .001). Confidence in both CVL placement and supervision improved post-intervention ( P = .03 each). Time required to obtain CVL access did not differ significantly pre and post intervention. The majority (20/21) believed there should be required competency testing for CVL placement. Conclusions: Pre-intervention dynamic US guided CVL competency was poor in this sample of attending critical care physicians but improved significantly with an instructional video intervention. This study suggests there is a role for procedural competency testing among attending critical care physicians, and that significant improvement is achievable with relatively minimal instruction.